A new blue-tailed Monitor lizard (Reptilia, Squamata, Varanus) of the Varanus indicus group from Mussau Island, Papua New Guinea - Weijola, Valter (Zookeys, 2016)
Abstract. We describe a new species of Varanus from Mussau Island, north-east of New Guinea. The new species is a member of the Varanus indicus species group and is distinguished from all other members by both morphological and molecular genetic characters. It is the third species of Varanus reported from the Bismarck Archipelago and the first record of a yellow tongued member of the Varanus indicus species group from a remote oceanic island. The herpetofauna of Mussau Island has not been well studied but the discovery of this new species is in accordance with recent findings indicating that the island may harbor several unknown endemic vertebrates. The distribution of the closely related Varanus finschi is also discussed in the light of recent fieldwork and a review of old records.